سيميائية توظيف التقنيات الرقمية في بنية أفلام الخيال العلمي: فيلم "Spider-Man: Far from Home" أنموذجا - عمارة، محمد محمد علي هندي (جامعة القاهرة - كلية الإعلام - مركز بحوث الرأي العام, 2021)
تهدف الدراسة إلى التعرف على التوظيف الدلالي للتقنيات الرقمية المستخدمة في بنية أفلام الخيال العلمي، وتحديد الدوال الأساسية المستخدمة في التعبير عن لقطات الكاميرا المختلفة، والكشف عن كيفية توظيف برنامج (CGI) للدمج بين العناصر الحقيقية والمصطنعة (الخيال/ الواقع)، ورصد الدلالات السيمولوجية للألوان المستخدمة في الفيلم. واستخدمت الدراسة أداة التحليل السيميولوجي. وتوصلت الدراسة إلى عدة نتائج: تم توظيف التقنيات والمؤثرات البصرية داخل المشهد بشكل مبدع وأعطت مصداقية وتشويق للفعل الدرامي، كما أسهمت المؤثرات في إضفاء الواقعية على الفعل الدرامي وكذلك إثارة وتشويق ودفع الصراع نحو الذروة، ومنحت المؤثرات الصوتية الصورة دلالاتها الواقعية وإعطاء الأفعال والأماكن والأحداث واقعيتها ووجودها، كما لعبت شدة الصوت في الفيلم دور كبير، ووفق المخرج في توظيف لغة الجسد لشرح العديد من المواقف وتدعيمها، كما تمكن الفيلم من التوظيف المتميز للديكور، فاستطاع أن يعكس المستوى الاجتماعي والثقافي والاقتصادي للشخصيات بنجاح، كما تناسبت مع البعد الزماني والمكاني للفيلم، كما نجح الفيلم في الاستخدام الجيد للملابس والإكسسوار والمكياج لإبراز صفات الشخصيات وخصائصها، ورسمها بشكل متقن ومتكامل، واستخدمت زوايا التصوير المنخفضة والمرتفعة لتوضيح مكانة الشخصيات أو لتدعيم موقفها في حدث معين سواء من تعظيم أو تحقير."
The study aims to identify the semantic employment of digital technologies used in the structure of science fiction films, to identify the basic functions used in expressing different camera shots, to reveal how the (CGI) program is used to combine real and artificial elements (fantasy / reality), and to monitor the semiological connotations of colors. Used in the movie. The study used the semiological analysis tool. The study reached several results: Techniques and visual effects within the scene were creatively employed and gave credibility and suspense to the dramatic action, as well as the effects contributed to imparting realism to the dramatic action as well as stimulating and suspense and pushing the conflict towards the climax, and the sound effects gave the picture its realistic connotations and giving the actions, places and events their realism and existence The intensity of the voice in the film played a big role, and the director was successful in employing body language to explain and support many situations, and the film was able to use the distinctive decoration, so it was able to successfully reflect the social, cultural and economic level of the characters, and it also matched the temporal and spatial dimension of the film. The film in the good use of clothes, accessories and make-up to highlight the characters' qualities and characteristics, and to draw them elaborately and in an integrated manner, and the low and high photography angles were used to clarify the status of the characters or to support their position in a specific event, whether from glorifying or belittling."
Keywords: علوم الإعلام والاتصال -- تكنولوجيا المعلومات -- الأفلام السينمائية -- أفلام الخيال العلمي